AN EXPLORATION OF THE DEMOTIVATIONAL FACTORS AFFECTING TEACHING AND LEARNING OF ENGLISH AS A FOREIGN LANGUAGE OF EFL LEARNERS IN GULF COUNTRIES - Gulnaz, Fahmeeda; Yusuf Mandouh, Sahar; Ahmad, Asif (PEOPLE: International Journal of Social Sciences, 2016)
Motivation is instrumental in successfully carrying out any activity while demotivation is a detrimental force that impedes the progress of any action or activity which has widely unveiled its diverse manifestations to EFL learners across the globe. Based on the reviewing of previous works and contexts, the present study aims at investigating the demotivational factors that significantly hamper learning of Arab EFL learners in classrooms in gulf countries. The work utilized triangulation in the use of research methods, i.e. both qualitative and quantitative methods overlap each other: (i) structured interview of experienced EFL (3 male and 4 female) teachers, with maximum open ended questions exhibit qualitative dimension of the study; (ii) opinionnaire developed with closed ended questions by employing Likert’s five point scale, represents quantitative perspectives of the work. The data was collected to investigate teacher’s teaching style and practices in EFL classrooms; teacher’s behavior and method of teaching; mismatches between the curriculum and the level and needs of the learners; crowded classes, use of unauthentic material; students’ inadequate elementary knowledge of four language skills and their lack of determination of goals and objectives to learn English language. All thesefactors call attention of the policy makers to revise and redesign the educational policies up to secondary level education.